PERANCANGAN BIOGAS MODEL LANDFILL GAS SEBAGAI BAHAN BAKAR ALTERNATIF - yusup Nur Rohmat; Sukroni Sukroni; Emin Haris; Tito Endramawan; Muhammad Andrian (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The use of cooking fuel, both in businesses and households, is essential, especially given the lack of alternatives to LPG following the fuel transition. The rise in global oil prices due to fuel shortages has become a global issue. Biogas, produced through the anaerobic fermentation of organic waste by bacteria, generates methane gas that can be utilized as an alternative energy source. Therefore, a landfill gas model biogas machine was designed to convert organic waste, such as cow manure and tofu liquid waste, into alternative fuel. The machine is equipped with a microcontroller system for automatic valve operation and gas pressure monitoring. Static load simulation on the machine frame using SolidWorks software showed that the maximum stress experienced was 10.4 x 10^6 N/m², well below the material's yield strength of 203.9 x 10^6 N/m², indicating safety. The displacement simulation on the machine frame ranged between 0.1–0.2 mm in the loaded areas, and the resulting factor of safety (FOS) was 19.5, signifying a highly safe design (FOS > 1).